Lilium huanglongense (Liliaceae): a newly-discovered species in north-western Sichuan, China - Ting Wang; Yumei Yuan; Ting-Hong Zhou; Yundong Gao (PhytoKeys)
In this study, we describe Lilium huanglongense, a newly-discovered lily species identified following extensive surveys in an undeveloped area of the Huanglong National Nature Reserve in Sichuan, China. This region, located in the Hengduan Mountains of south-western China, is recognised as one of the world’s prominent biodiversity hotspots, providing diverse habitats for a wide range of plant species. Morphologically, L. huanglongense resembles Lilium fargesii Franch., which is distributed in central China, as well as other tepal-recurved members of the section Lophophora (Bureau & Franch.) F. T. Wang & Ts. Tang. This section comprises dwarf lilies predominantly found in the alpine scrub of the Hengduan Mountains, extending westwards into the Himalayas. Molecular phylogenetic analyses using both nuclear ITS and chloroplast genomes confirm the independent status of the new species and its placement within the section Lophophora. The identification of this new species helps to fill the distribution gap between broad-leaved forest and alpine scrub species within the section, thereby enhancing our understanding of the diversity and distribution history of Lophophora.